Desain dan Implementasi Sistem Operasi Linux Ubuntu Versi 22.04 untuk Perlindungan Data dari Serangan Komputasi Kuantum - Rakhmadi Rahman; Awal Ramadhan Nasrun; Adinda Aulia Rahmi (Asosiasi Profesi Telekomunikasi Dan Informatika Indonesia, 2024)
The development of quantum computing presents new challenges to the security of data stored and processed by today's computer systems. Quantum computers have the ability to perform calculations at very high speeds, which could threaten the security of currently used encryption algorithms. Therefore, steps are needed to design and implement an operating system that is able to protect data from quantum computing threats. Ubuntu Linux version 22.04, as one of the leading open source Linux distributions, offers high-level security features. To face the era of quantum computing, it is necessary to carry out special development and implementation of this operating system. This research aims to improve the security of the Ubuntu Linux operating system version 22.04 so that it can withstand quantum computing attacks by designing and implementing a quantum-resistant cryptography protocol and testing the security and performance of the resulting system. This research method uses a qualitative approach and research and development (R&D) with literature studies. The research results show that the integration between Liboqs and OpenSSL on Linux Ubuntu 22.04 successfully implements a cryptographic algorithm that is resistant to quantum computing. Although there is a slight performance increase due to the additional overhead of the quantum algorithm, the security of the system in protecting data from quantum computing attacks is proven to be well maintained.